2015
DOI: 10.1371/journal.pone.0127047
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Molecular Mechanisms of Hepatic Injury in Rats under Simulated Weightlessness and the Protective Effects of Resistance Training

Abstract: This study investigated the effects of long-term simulated weightlessness on liver morphology, enzymes, glycogen, and apoptosis related proteins by using two-month rat-tail suspension model (TS), and liver injury improvement by rat-tail suspension with resistance training model (TS&RT). Microscopically the livers of TS rats showed massive granular degeneration, chronic inflammation, and portal fibrosis. Mitochondrial and endoplasmic reticulum swelling and loss of membrane integrity were observed by transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1
3

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 37 publications
2
25
1
3
Order By: Relevance
“…Bax acts downstream in the mitochondrial apoptotic pathway and it represents a key molecule in this process. As a component of the mitochondrial electron transfer chain, cytochrome c can initiate caspase activation following its release from mitochondria, binding to Apaf-1 ( Du et al, 2015 ). Afterward, Apaf-1-cytochrome c complex forms apoptosome, which recruits procaspase-9 and initiates the formation of the caspase-9 holoenzyme that cleaves and activates downstream caspases, such as caspase-3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bax acts downstream in the mitochondrial apoptotic pathway and it represents a key molecule in this process. As a component of the mitochondrial electron transfer chain, cytochrome c can initiate caspase activation following its release from mitochondria, binding to Apaf-1 ( Du et al, 2015 ). Afterward, Apaf-1-cytochrome c complex forms apoptosome, which recruits procaspase-9 and initiates the formation of the caspase-9 holoenzyme that cleaves and activates downstream caspases, such as caspase-3.…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, Apaf-1-cytochrome c complex forms apoptosome, which recruits procaspase-9 and initiates the formation of the caspase-9 holoenzyme that cleaves and activates downstream caspases, such as caspase-3. Furthermore, the recruitment of Bax leads to permeabilization of mitochondrial outer membrane ( Wang, 2001 ; Du et al, 2015 ), which is considered one of the key control switches of the apoptotic process ( Ferreira et al, 2008 ). Here, we demonstrated that cytochrome c was released into the cytosol in the inoculated group, and this represents a biomarker indicating the activation of the mitochondrial apoptotic pathway ( Pan et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The animals were treated as previously described ( 13 ). Briefly, Male Wistar rats (Eight-week-old, approximately 250 g) were purchased from the Experimental Animal Center, Academy of Military Medical Sciencs.…”
Section: Methodsmentioning
confidence: 99%
“…As in this study, once the expression of pro-apoptotic proteins such as Bax and Bak or of antiapoptotic proteins such as Bcl-2 and Bcl-xl was altered, cytochrome c would be released from the intermembrane space. As a component of the mitochondrial electron transfer chain, cytochrome c could initiate caspase activation, including caspase 9 and caspase 3, ultimately induced apoptosis in hepatic injury [43]. A number of studies reported that p38 MAPK and AKT were activated by ROS and cytokines [44][45][46].…”
Section: Discussionmentioning
confidence: 99%